RECURRENT EPISCLERITIS IN CHILDREN-LESS THAN 5 YEARS OF AGE - Shah, Syed Ashfaq Ali; Kazmi, Hassan Sajid; Awan, Abdul Aziz; Khan, Jaffar (Journal of Ayub Medical College Abbottabad, 2006)
Background: Episcleritis , though common in adults, is a rare disease in children. Episcleritis is associated with systemic diseases in a third of cases in adults. Here we describe systemic diseases associated with recurrent episcleritis in children less than five years of age. Method: This Retrospective Observational case series study was conducted at the Department of Ophthalmology of Ayub Teaching Hospital, Abbottabad, from March 1995 till February, 2006. Six children diagnosed clinically with recurrent episcleritis were included in this study. Complete ophthalmologic as well as systemic evaluation was done in each case. Results: This study was conducted on 6 children with a diagnosis of recurrent episcleritis. There were four boys and two girls, with an age range of 35-52 months. Right eye was involved in three cases, left eye in two cases while one case had a bilateral disease. Recurrence occurred in the same eye in all cases, with one bilateral involvement. Four children (66%) had a history of upper respiratory tract infection in the recent past. No other systemic abnormality was detected in any case. Two cases had a history of contact with a pet animal. Conclusion: Recurrent episcleritis in young children is a benign condition. Upper respiratory tract infection is the most common systemic association. Pet animals may be a contributory factor. Keywords: Recurrent Episcleritis, Children, Age, Systemic Disease.